2014
DOI: 10.1016/j.enbuild.2013.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, appliance-level electricity use feedback system: How to engage users?

Abstract: a b s t r a c tEngage is a rapidly deployable, retrofit energy monitoring system developed for direct support of a novel energy use behavior investigation and a large-scale deployment in campus apartments. We describe the end-to-end system and report results related to web dashboard engagement during a year-long experiment. The objective was to determine user engagement with real-time and easily accessible information about personal energy consumption. Leveraging low-cost components, this system was designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Bathrooms are shared between rooms and were not monitored by the experiment. More information on the technology is provided in Chen et al (2014).…”
Section: Location and Technologymentioning
confidence: 99%
“…Bathrooms are shared between rooms and were not monitored by the experiment. More information on the technology is provided in Chen et al (2014).…”
Section: Location and Technologymentioning
confidence: 99%
“…Emeakaroha et al (2014) [8], R.K. Jain et al (2013) [9], H.-M. Chen et al (2012) [10], V.L. Chen et al (2014) [11], P.M. Johnson et al (2010) [12], and M.J. Bekker et al (2010) [13]. Results are summarized in Table 1.…”
Section: Studies and Methodologymentioning
confidence: 93%
“…They set up this feedback in two adjacent V.L. Chen et al [11] proposed a feedback architecture to monitor separately HVAC, lighting and wall socket electrical energy. They found that 80% of dashboard activity was generated by 25% of students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations